PERAN KECERDASAN SPIRITUAL DAN EMOSIONAL MAHASISWA DALAM MEMAHAMI ILMU AKUNTANSI - Moch Rizki Alfian; M. Elfan Kaukab; Romandhon Romandhon (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
This study examines the role of spiritual intelligence and emotional intelligence in FEB UNSIQ Wonosobo students. The competence and professionalism variables of the lecturers were also investigated. The sampling technique used a purposive sampling technique, obtained a sample of 141 respondents. Data analysis in this study used a multiple linear regression method. The results of this study indicate that lecturer competence, spiritual intelligence, and emotional intelligence have a significant effect on the level of understanding of accounting science, while the professionalism of lecturers does not affect the level of understanding of accounting. The limitation of this study is the low determination value of 27% so that the results of this study can be explored further with new variables.